Establishment of Strict Liability for Motor Vehicle under Ethiopian Law: Issues of Concern - Chane, Gizachew Silesh; Fekadu, Fekerabenet (Bahir Dar University Journal of Law, 2022)
Due to frequent happening of accidents and their severe impact on the victims, court disputes pertaining to liabilities for motor vehicles are not only considerable in amount but also ever increasing in number. Unfortunately, some provisions governing strict liability for motor vehicles are either silent or vague or too general. These factors led to disparities in the application of laws governing strict liability for motor vehicles, particularly on issues related to the establishment of strict liability. This paper, thus, inter alia, raises the following questions: What is the scope of the law governing strict liability for motor vehicles? How the advent of a law on third party insurance against motor vehicle victim affects the scope of strict liability law? Who can be plaintiff and defendant under strict liability law? To address these issues, qualitative research approach which employs legal analysis, interview, and literature and case reviews is used. The finding concluded that laws governing establishment of strict liability for motor vehicles are neither adequate to regulate current dispute nor be able to anticipates possible future developments. Hence, for uniform and proper application of laws governing establishment of strict liability for motor vehicles, amendment of relevant provisions needs to be made, until then, the Federal Supreme Court Cassation bench shall provide guidance through interpreting vague and general provisions in light of theories of strict liability.